Nilai Budaya dalam Serat Ajisaka - Erlin Kartikasari (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
One of Javanese literature attached to Javanese people is the story of Ajisaka, which was published among the people in verbal and writing. Ajisaka is a Javanese figure whom the Javanese people consider as the originator of Javanese script. One of the recorded of the story of Ajisaka was the Serat Ajisaka written by J. Kats using Javanese script. Serat Ajisaka is one of the stories from a collection of stories in the book entitled Serat Jawi Tanpa Sekar written by J. Kats, a Dutch writer in 1942. This research aims to describe the cultural values ​​in Serat Ajisaka by J. Kats in 1942 using philology studies. This research uses the descriptive method conducted in three stages, the first stage transcribing data, the second stage transliterating Latin script containing Javanese into Indonesian, then analyzing the cultural value in Serat Ajisaka. Serat Ajisaka has several concepts of cultural values, namely: 1) educational values, 2) religious values, 3) leadership values, 4) heroism values, 5) courage values, 6) simplicity values, 7) mutual-cooperation values, 8) moral values, and 9) the value of sacrifice for others.